PH-Dependent structural diversity of a 2-pyridinemethanol Cu complex and its relatively strong magnetic exchange coupling via hydrogen bonding. Issue 19 (25th April 2017) - Hamaguchi, Tomohiko; Nagata, Tomoko; Hayami, Shinya; Kawata, Satoshi; Ando, Isao
Abstract : pH-Dependent structural diversity of a 2-pyridinemethanol Cu complex and its relatively strong magnetic exchange coupling via hydrogen bonding is reported. Abstract : The diversity of the self-assembled structures of a Cu complex via hydrogen bonding, including a square planar unit, is reported. The Cu complex forms two self-assembled structures by hydrogen bonding, depending on the acidity of the recrystallization conditions. A linear chain structure can be produced under acidic conditions, and a three-dimensional network structure is observed under basic conditions. The linear chain structure is constructed from intermolecular sharing of a hydrogen atom between two 2-pyridinemethanolate units, with an O⋯O distance of 2.412(1) Å and an O–H–O bond angle of 170(3)°. The linear chain structure exhibits relatively strong magnetic coupling ( J = −9.91(2) cm −1 ) via hydrogen bonding between Cu atoms; this coupling was also confirmed by electron spin resonance experiments. Thermochromic behavior was also observed for the complex.